The legal nature of the rules of carriage of persons in public transport - Masternak, Marian; Masternak, Marta Maria (Studia Iuridica Toruniensia, 2021)
Rules of a carriage of persons in public collective transport are acts regulating the rights and obligations of entities providing public collective transport services and persons using these services. Due to the fact that they are unilaterally established by the organizers of collective public transport and entities providing transport services as part of their public tasks, the question arises whether these regulations should be treated as activities in the sphere of private law or in the field of public administration. The doctrine and case-law is convinced that the regulations in question are a pattern of contract in the meaning of civil law. This position, although supported by valid arguments, does not fully take into account the specificity of collective public transport, which is a public activity carried out by public administration entities and private persons entrusted with performing public tasks. Therefore, it seems reasonable to start a discussion on the need to apply to the regulations of public transport collective legal structures based not only on civil law, but also on administrative law.